2014
DOI: 10.1039/c4ta00121d
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized mesoporous structured inorganic materials as high temperature proton exchange membranes for fuel cells

Abstract: High temperature proton exchange membrane fuel cells based on functionalized mesoporous silica nanocomposite membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 177 publications
(243 reference statements)
1
40
0
1
Order By: Relevance
“…In addition, the fuel cell performances of resultant membranes drop gradually at high current density region due to the decrease of the voltage caused by the increased gas mass transfer resistance. Similar observations have been found in other literatures[60][61][62][63].…”
supporting
confidence: 91%
“…In addition, the fuel cell performances of resultant membranes drop gradually at high current density region due to the decrease of the voltage caused by the increased gas mass transfer resistance. Similar observations have been found in other literatures[60][61][62][63].…”
supporting
confidence: 91%
“…Entry 7 and entry 12 show that the catalytic activity slightly dropped when the doped amount was more than 1:1 both for Cu and Fe. Interestingly, it can be observed that Cu and Fe simultaneously doped to SiW11O39 showed a better catalytic activity both for conversion and selectivity than pure SiW11O39 and single Cu or Fe-doped SiW11O39 samples (entries[13][14][15][16]. Among four Cu/Fe-codoped catalysts, Cu1.00Fe1.00SiW11 exhibited the highest activity with 98.0 % conversion and 98.3 % selectivity in benzyl alcohol selective oxidation to benzaldehyde.…”
mentioning
confidence: 92%
“…213). Moreover, proton-conducting mesoporous materials, such as phosphotungstic-acid-functionalized mesoporous silica, have shown great potential as membranes for fuel cells that operate at elevated temperatures because of their outstanding stability and efficient proton conductivity at temperatures higher than 100 °C and under low humidity 214,215 .…”
Section: Fuel Cellsmentioning
confidence: 99%